Effect of Grovth Medium on L-Dopa and Dopamine Production Using Citrobacter freundii (NRRL B-2643) - Çakmak, Meltem; Selen, Veyis; Özer, Dursun; Karatas, Fikret; Saydam, Sinan (My University, 2022)
In this study, microbial production of L-Dopa and Dopamine which is an important substrance for the treatment of Parkinson's disease were investigated by using Citrobacter freundii (NRRL B-2643). The effects of carbon source (sucrose) and, salt concentrations (NaCl, CaCl2), initial pH, temperature, inoculum level and shaking speed on L-Dopa and dopamine production were investigated. The amounts of extracellular L-dopa and dopamine were determined by using HPLC. Maximum L-dopa and dopamine production, under optimized conditions (sucrose: 2.5 g/L, NaCl and CaCl2: 1.0 g/L, inoculum level: 1.0% (v/v), initial pH: 6.5, temperature: 33°C, shaking speed: 200 rpm) were found to be 458 and 592 mg/L, respectively. Although the experiments were carried out for 60 hours, but the maximum production of L-Dopa and Dopamine was realized at around the 30th hour of the experiments.
Keywords: HPLC; Citrobacter; Dopamine; Fermentation; L-Dopa; freundii (NRRL B-2643)